PEMBELAJARAN TEMATIK BERMUATAN SBDP MATERI LAGU DAERAH SERAWAI SEBAGAI UPAYA PENANAMAN APRESIASI BUDAYA LOKAL DI KELAS IV SD NEGERI 49 BENGKULU SELATAN Yuvela Oktiara - Yuvela Oktiara; Bambang Parmadi; Pebrian Tarmizi (JURIDIKDAS, 2021)
This research aims to describe the thematic learning process containing cultural arts and crafts material for Serawai regional songs as an effort to instill appreciation of local culture in the fourth grade In SD Negeri 49 Bengkulu Selatan and describe the form of student appreciation during thematic learning containing cultural arts and crafts material for Serawai regional songs as an effort to inculcate local cultural appreciation in the fourth grade SD Negeri 49 Bengkulu Selatan. This research uses qualitative research with descriptive study method. The research subjects were classroom teachers and fourth grade students at SD Negeri 49 Bengkulu Selatan. The research instrument used observation guidelines, interview guidelines, questionnaire sheets and documentation studies. Data collection techniques using observation, interviews, questionnaires and documentation. Data analysis through data collection, data reduction, data presentation, conclusion and verification.The results of this study are: 1). The process of learning local songs has been going well. Learning local songs can instill student appreciation. Students become aware of the title of local songs, students have knowledge of how to sing local songs, students can sing local songs, students can interpret the lyrics of local songs. 2) The form of student appreciation when learning local songs is in the good category. Students can assess the appearance of friends who are singing folk songs in front of the class, students observe the appearance of friends and can explain the appearance of other friends in singing local songs, and so on. Based on the results of the study, it was concluded that the thematic learning with cultural arts and crafts content for the Serawai regional song material effectively and efficiently helped students to be actively involved in learning.